Role of bulking agents in bladder exstrophy-epispadias complexes - Seyed Mohammad Vahid Hosseini; Mohammad Zarenezhad; Sakineh Falahi; Ali Amir Ahmadi; Babak Sabet; Ahmad Reza Rasekhi (Wolters Kluwer Medknow Publications, 2013)
Background: Role of pelvic osteotomy in surgical management of bladder exstrophy is controversial But pelvic rim closure importantly. Bulking agents have been used for perineal and pelvic dysfunction in adults. In this study, bladder extrophy repair was performed without pubic closure And bulking agent injections were used as the strut of anterior pelvis for prevention of Organ prolapse and other functions in this series. Patients and Methods: During the period 2008-2012, twenty-five exstrophy-epispadias complex patients with a mean age of 14 months underwent surgical reconstruction. Rectus abdominis Muscle was detached from the superior pubis and sutured to each other in the midline and Re-anchored at the pubis and 8-9 month later urethra was constructed and placed between prineal muscles. Bladder neck repair and intersyphyseal reconstruction was done With bulking agents one year after primary bladder closure when in our series bladder Prolapse mainly occurred. One to 4 mL of bulking agents polyacrylate (vantris/promedon) was injected at the level of the intersymphyseal area and opening on either sides of the urethra. Results: Mean urinary continence score, before, 3 and 6months after injection Were (2.65 ± 074),(1.95 ± 082),(1.75 ± 0.78), respectively.(p < 0.001). The correlation factor Between before injection, 3 and 6 months were % 82, % 74 spectively. Meancapacity of bladder before, 3, 6 months after injection were (31 ± 14.01), (41 ± 12.81), (56 ± 11.98) mml, respectively. The correlation factor before and after injection were 59%. Comparing the CS and CB between male and female before and after Injection were significant. (p < 0.001) but correlation factor in male 99% and Female 74%. Three out of five girls had improved bladder prolapse. There was no Complication, infection or migration of bulking agents. Patients had increased in soft tissue according to MRI. Conclusion: Using bulking agents is a good alternative to sling pelvic floor not only cosmetically but also for ease of patients and operation.